Boundedness on Triebel-Lizorkin and Lebesgue Spaces of Multilinear Singular Integral Operators Satisfying a Variant of Hörmander’s Condition (Analysis in Theory and Applications, 2022)
The boundedness on Triebel-Lizorkin and Lebesgue spaces of the multilinear operators associated to some singular integral operators satisfying a variant ofHörmander’s condition are obtained.